(3OQI Gdafhf aj QDjI bQI GdYjhf aj QDjG GdefGe GdLGQi eLQi GdEdgGes - (3YHO GdQMef Hf eMeO Hf Ydj Hf CMeO Hf eMeO GdHSWGej GdMfaj, Rjf GdOjf,J (B858 (3g` s
(3ChdgG (B:s
(3CMeO Ydi eG GWdY ef SeGA QMeJg TehS GSeGFg hCbeGQ MceJg BjI ddEgJOGA s
(3BNQgG (B:s
(3hGdUdGI Ydi WQI VjGA GdhLhO hZQI HgGA GdTghO eG fGLJ GdhQbGA ai ChQGb GdQjGV hdGMJ GdYfbGA ai BaGb GdZjGV s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B331 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B184s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeI (B- (3U (B126 s
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK (B(3167) s
Keywords: (3JYHjQ GdQDjGs